Sestrin2 Protects Dopaminergic Cells against Rotenone Toxicity through AMPK-Dependent Autophagy Activation - Hou, Yi-Sheng (Mol Cell Biol, 2015)
Dysfunction of the autophagy-lysosomal pathway (ALP) and the ubiquitin-proteasome system (UPS) was thought to be an important pathogenic mechanism in synuclein pathology and Parkinson's disease (PD). In the present study, we investigated the role of sestrin2 in autophagic degradation of α-synuclein and preservation of cell viability in a rotenone-induced cellular model of PD. We speculated that AMP-activated protein kinase (AMPK) was involved in regulation of autophagy and protection of dopaminergic cells against rotenone toxicity by sestrin2. The results showed that both the mRNA and protein levels of sestrin2 were increased in a TP53-dependent manner in Mes 23.5 cells after treatment with rotenone. Genetic knockdown of sestrin2 compromised the autophagy induction in response to rotenone, while overexpression of sestrin2 increased the basal autophagy activity. Sestrin2 presumably enhanced autophagy in an AMPK-dependent fashion, as sestrin2 overexpression activated AMPK, and genetic knockdown of AMPK abrogated autophagy induction by rotenone. Restoration of AMPK activity by metformin after sestrin2 knockdown recovered the autophagy activity. Sestrin2 overexpression ameliorated α-synuclein accumulation, inhibited caspase 3 activation, and reduced the cytotoxicity of rotenone. These results suggest that sestrin2 upregulation attempts to maintain autophagy activity and suppress rotenone cytotoxicity through activation of AMPK, and that sestrin2 exerts a protective effect on dopaminergic cells.